Empowering MSMEs in South Sumatra: The role of digital transformation - Hermawati, Lisa; Pusvita, Ema; Khairunnisa, Delta; Putri, Aning K`usuma (Annals of Human Resource Management Research, 2025)
Purpose: This study aimed to examine the relationship between resilience and sustainability of culinary MSEs through digital transformation in South Sumatra Province. Research Methodology: Sample selection with criteria, namely respondent had been having business for at least 5 years, had passed fluctuating conditions such as surviving covid conditions, rising inflation, monetary policy and so on. The number of samples was 130 MSEs, which were local culinary businesses. Knowing the relationship of each variable X to variable Y was tested using structural equation Modelling (SEM-PLS) analysis. Results: This study found a resilience relationship with digital transformation of 0.834 and a sustainability relationship with digital transformation of 0.400. The relationship between resilience and digital transformation was stronger than that between sustainability and digital transformation. The main cause was that MSEs lacked long-term commitment, and it was difficult for them to grow in dynamic environmental and social conditions while also focusing on profits. Digital transformation in MSEs was defensive rather than supporting holistic sustainability, limited sustainable resources simultaneously, and integrated with digital transformation. Therefore, MSE actors need to be educated, trained, and given guidance in changing mindset and social behavior for the long-term sustainability of MSEs. Limitations: The study was limited to culinary MSEs in South Sumatra and used non-probability sampling, which may have affected generalizability. Contribution: This study revealed that resilience had a stronger influence than sustainability in driving digital transformation among culinary MSEs. Novelty: This study offers a novel perspective by integrating resilience and sustainability in analyzing digital transformation within culinary MSEs.